Stock Liquidity Analysis Before And After The Announcement Of Split Reverse Stock On Indonesia Stock Exchange Companies 2017-2020 - Hamdana (JEKAMI Journal of Accounting, 2021)
The purpose of this study is a type of quantitative research with the aim of knowing whether there is a significant difference in stock liquidity before and after the announcement of the reverse stock split on the Indonesia Stock Exchange company in 2017-2020. The sample data obtained in this study are companies listed on the Indonesia Stock Exchange that carried out a stock split in 2017-2020. The sample obtained from 2017-2020 which experienced a stock split was 38 companies. The data collection technique used secondary data which was analyzed by using the Paired Sample t-Test. The results showed that there was no significant difference before and after the announcement of the stock split, by calculating the statistical test through the SPSS application. Based on the data obtained from the data difference test, the data is normally distributed and for the paired sample t-Test test which shows there is no significant difference before and after the stock split.